Compliance of World Health Organization Surgical Safety Checklist in a Tertiary care Hospital in Nepal - Prospective Observational Study - Shah, Aashish; Basukala, Sunil; Kunwar, Bhuban Raj; Thapa, Puja; Thapa, Niranjan (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: The World Health Organization (WHO) introduced the Surgical Safety Checklist in 2008, aiming to improve patient safety during surgical procedures. Despite guidelines and protocols for patient safety, compliance with these safety measures remains a concern, particularly in underdeveloped and developing countries. Methods: This cross sectional study was conducted at Shree Birendra Hospital, Kathmandu, Nepal over six months. It included 400 patients undergoing elective surgical procedures, with data collected from various departments. Compliance with the WHO Surgical Safety Checklist was evaluated based on the Sign-In, Time-Out, and Sign-Out phases. Statistical analysis was performed using IBM SPSS version 24.0. Results: The study found an overall compliance rate of 312 (78%) with variations across different checklist phases. The study covered a range of specialties, with the highest number of cases in General and GI surgery156 (39%). Compliance with the Sign-In phase varied for different checklist items, with some showing incomplete compliance. During the Time-Out phase, confirmation of team member introductions and antibiotic prophylaxis administration had varying levels of compliance. In the Sign-Out phase, there were discrepancies in oral confirmations and equipment-related problems. Conclusion: This study highlights areas requiring improvement in checklist compliance in the studied tertiary care hospital. It serves as a valuable model for similar assessments in healthcare institutions and underscores the importance of prioritizing patient safety in surgical procedures.